Aldosterone-induced cardiac damage in primary aldosteronism depends on its subtypes. Issue 1 (January 2021) - Higuchi, Satoshi; Ota, Hideki; Tezuka, Yuta; Seiji, Kazumasa; Takagi, Hidenobu; Lee, Jongmin; Lee, Yi-Wei; Omata, Kei; Ono, Yoshikiyo; Morimoto, Ryo; Kudo, Masataka; Satoh, Fumitoshi; et al.
Abstract : Objectives: This study compared cardiac function, morphology, and tissue characteristics between two common subtypes of primary aldosteronism (PA) using a 3T MR scanner. Design: A retrospective, single-center, observational study. Methods: We retrospectively reviewed 143 consecutive patients with PA, who underwent both adrenal venous sampling and cardiac magnetic resonance. We acquired cine, late gadolinium enhancement, and pre- and postcontrast myocardial T1-mapping images. Results: PA was diagnosed as unilateral aldosterone-producing adenoma (APA) in 70 patients and bilateral hyperaldosteronism (BHA) in 73. The APA group showed significantly higher plasma aldosterone concentration (PAC) and aldosterone to renin rate (ARR) than the BHA group. After controlling for age, sex, antihypertensive drugs, systolic and diastolic blood pressure, and disease duration, the parameters independently associated with APA were: left ventricular end-diastolic volume index (EDVI: adjusted odds ratio (aOR) = 1.06 (95% CI: 1.030–1.096), P < 0.01), end-systolic volume index (ESVI: 1.06 (1.017–1.113), P < 0.01), stroke index (SI: 1.07 (1.020–1.121), P < 0.01), cardiac index (CI: 1.001 (1.000–1.001), P < 0.01), and native T1 (1.01 (1.000–1.019), P  = 0.038). Weak positive correlations were found between PAC and EDVI (R = 0.28, P < 0.01), ESVI (0.26, P < 0.01), and SI (0.18, P = 0.03); and between ARR and EDVI (0.25, P < 0.01), ESVI (0.24, P < 0.01), and native T1 (0.17, P  = 0.047). Conclusions: APA is associated with greater LV volumetric parameters and higher native T1 values, suggesting a higher risk of volume overload and myocardial damage.